Teen Gambling: Understanding a Growing Epidemic - Derevensky, Jeffrey L. (Rowman & Littlefield Publishers, 2012)
Never before in our history have we witnessed such an explosion of worldwide gambling opportunities. Our love affair with gambling points to its widespread appeal as a socially acceptable leisure activity. However, gambling, once thought to be strictly an adult activity, has become an increasingly popular pastime among adolescents. Whether engaged in wagering on games of personal skill, poker amongst friends, purchasing lottery tickets, sports wagering, casino gambling, or gambling over the Internet, its popularity among the young is on the rise. There is growing evidence that large numbers of adolescents remain actively involved and engaged in almost all forms of both regulated and unregulated gambling activities in spite of age restrictions. While gambling addiction is recognized as a psychiatric disorder, there is a common misconception that adults are the only sufferers. Yet data from around the world point to high levels of gambling problems amongst adolescents, with rates of adolescent gambling problems being between 2-4 times those of adults. Based upon a growing body of evidence, this book provides a better understanding of our current knowledge concerning the causes and extent of youth gambling problems. Using real life examples, Derevensky shows how adolescents gain access to gambling activities, what issues arise from those activities, and the tools we have available for assessing problem gambling among youth. He provides clear and practical strategies for the prevention and treatment of youth with gambling problems and points the way to understanding the extent and consequences of enabling youth gambling.